Factors predicting self-compassion among patients with breast cancer undergoing chemotherapy in Thailand: A cross-sectional study - Krutchan, Nisa; Skulphan, Sombat; Thapinta, Darawan; Thungjaroenkul, Petsunee; Saengthong, Songserm (Belitung Raya Publisher - Belitung Raya Foundation, 2024)
Background: Breast cancer is the most common female malignancy. Although chemotherapy is the primary treatment for breast cancer, it frequently has several detrimental side effects. Patients with breast cancer require self-compassion to regulate their emotions in order to cope with their suffering. Factors affecting self-compassion have mostly been investigated in the context of chronic diseases in general, not specifically in relation to patients receiving chemotherapy for breast cancer. Objective: This cross-sectional study sought to describe the self-compassion level and to examine the predictive ability of self-critical judgment, body image, stress, attachment style, social support, hope, and self-reassuring on self-compassion among patients with breast cancer undergoing chemotherapy. Methods: The participants were 210 Thai women with breast cancer who received chemotherapy in northern Thailand and were selected using proportionate random sampling. Data were collected from December 2021 to January 2023 using validated instruments. Data were analyzed using descriptive statistics and hierarchical regression analysis. Results: Self-compassion was moderate (Mean = 2.91, SD = 0.91). Self-critical judgment (β = 0.487, p <0.001) and hope (β =0.128, p = 0.032) could predict self-compassion in patients with breast cancer undergoing chemotherapy and explained 40.1% of the variance. Conclusion: The study’s findings highlight the importance of addressing self-critical judgment and fostering hope in patients with breast cancerundergoing chemotherapy to enhance their self-compassion. Nurses and other healthcare providers can use the findings to provide interventions to promote self-compassion.